Lentiviral vector integration in the human genome induces alternative splicing and generates aberrant transcripts - Moiani, Arianna; Paleari, Ylenia; Sartori, Daniela; Mezzadra, Riccardo; Miccio, Annarita; Cattoglio, Claudia; Cocchiarella, Fabienne; Lidonnici, Maria Rosa; Ferrari, Giuliana; Mavilio, Fulvio (The Journal of clinical investigation, 2012)
Retroviral vectors integrate in genes and regulatory elements and may cause transcriptional deregulation of gene expression in target cells. Integration into transcribed genes also has the potential to deregulate gene expression at the posttranscriptional level by interfering with splicing and polyadenylation of primary transcripts. To examine the impact of retroviral vector integration on transcript splicing, we transduced primary human cells or cultured cells with HIV-derived vectors carrying a reporter gene or a human β-globin gene under the control of a reduced-size locus-control region (LCR). Cells were randomly cloned and integration sites were determined in individual clones. We identified aberrantly spliced, chimeric transcripts in more than half of the targeted genes in all cell types. Chimeric transcripts were generated through the use of constitutive and cryptic splice sites in the HIV 5ι long terminal repeat and gag gene as well as in the β-globin gene and LCR. Compared with constitutively spliced transcripts, most aberrant transcripts accumulated at a low level, at least in part as a consequence of nonsense-mediated mRNA degradation. A limited set of cryptic splice sites caused the majority of aberrant splicing events, providing a strategy for recoding lentiviral vector backbones and transgenes to reduce their potential posttranscriptional genotoxicity.